Association of Brain Metastases With Immune Checkpoint Inhibitors Efficacy in Advanced Lung Cancer: A Systematic Review and Meta-Analysis - Wang, Yanning; Zhang, Qianning; Chen, Chuansheng; Hu, Yuxuan; Miao, Liyun; Zhou, Yujie (Frontiers in Oncology, 2021)
Background: In pivotal immunotherapy trials, the efficacy of immune checkpoint inhibitors as treatments for lung cancer patients with brain metastases remains controversial. The aim of this study was to assess the relative efficacy of immunotherapy versus standard systemic therapy in advanced lung cancer patients with and without brain metastases. Methods: Systematic searches of PubMed, Embase, Cochrane database, and conference proceedings up to Aug 6, 2020 without year and language restrictions. The main outcomes were the overall survival in patients with and without brain metastases measured by hazard ratios, and the difference in efficacy between patients with and without brain metastases was measured by ratio of hazard ratios. Results: Nine eligible randomized controlled trials involving 6241 patients (682 [11%] with brain metastases and 5559 [89%] without brain metastases) were included in the analysis. A survival benefit of immunotherapy was observed for both patients with brain metastases (HR, 0.75; 95%CI, 0.53-0.97; P = .026) and patients without brain metastases (HR, 0.75; 95%CI, 0.67-0.83; P < .001). However, patients without brain metastases benefit more from immunotherapy than patients with brain metastases (HR, 1.37; 95%CI, 1.15-1.63; P = .001). Additionally, subgroup analyses indicated that tumor type affect the efficacy of immunotherapy in patients with brain metastases (HR, 1.04 vs 1.54; interaction, P = .041). Conclusions: Immunotherapy can significantly improve overall survival for advanced lung cancer patients with asymptomatic brain metastases, especially in patients with non-small-cell lung cancer, but the magnitude of benefit is brain metastases dependent.